2022
DOI: 10.1002/acm2.13596
|View full text |Cite
|
Sign up to set email alerts
|

Fiducial marker position affects target volume in stereotactic lung irradiation

Abstract: Real-time tracking systems of moving respiratory targets such as CyberKnife,Radixact,or Vero4DRT are an advanced robotic radiotherapy device used to deliver stereotactic body radiotherapy (SBRT). The internal target volume (ITV) of lung tumors is assessed through a fiducial marker fusion using four-dimensional computed tomography (CT). It is important to minimize the ITV to protect normal lung tissue from exposure to radiation and the associated side effects post SBRT. However, the ITV may alter if there is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…They suggested that an FM inserted within 30 mm of the lung tumor represented tumor motion with an error within 3 mm in many patients. These reports 25,30,31 on intrafractional variation support our findings: D max values of the FMs for D p ≤ 26 mm were smaller than those of the FMs for D p > 26 mm in all directions. Considering our results, the prior reports on intra-fractional variation, 25,30,31 and the distance from the tumor where the FM can be inserted into the bronchus, 26 mm may be a reasonable distance between the FM and the lung tumor.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…They suggested that an FM inserted within 30 mm of the lung tumor represented tumor motion with an error within 3 mm in many patients. These reports 25,30,31 on intrafractional variation support our findings: D max values of the FMs for D p ≤ 26 mm were smaller than those of the FMs for D p > 26 mm in all directions. Considering our results, the prior reports on intra-fractional variation, 25,30,31 and the distance from the tumor where the FM can be inserted into the bronchus, 26 mm may be a reasonable distance between the FM and the lung tumor.…”
Section: Discussionsupporting
confidence: 90%
“…Only a few studies have indicated the specific distances between tumors and FMs. 25,30,31 Akasaka et al 25 analyzed the three-dimensional distance of the coiled FM to the lung tumor in CT scans for planning at the expiratory and inspiratory phases (D diff ) and the ratio of ITV to gross tumor volume (GTV) (ITV/V GTV ) created by 4D-CT and CT scans at the inspiratory phase for treatment planning. They showed that D diff and ITV/V GTV were smaller when the distance between the edges of the tumor and the FM was less than 10 mm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations